A new biometric template protection based on secure data hiding approach - Khalaf, Emad Taha; Norrozila, Sulaiman (Asian Research Publishing Network (ARPN), 2015)
Biometrics is a technology that has been widely used in many official and commercial identification applications. The extracted features from the biometric sample is called biometric template which is used during a biometric authentication process. The security of templates is the critical part of biometric system and one of the most crucial issues in designing a secure system. The proposed approach focused on combining data hiding and biometrics to take advantage of the benefits of both fields and develop the hiding technique to find a secure solution for protecting biometric data. We deal with dental as a first biometric source and a user's speech as a second biometric source at same time it a reliable key from a user's speech for enhanced the security of the system. Two of the popular methods are combined DWT and DCT in the proposed security system (SDHA) for embedding and extraction the secret data in order to compensate the drawbacks of both of them and to make the hidden information much more secure against the attacks, Wavelet Transform which use Dyadic Filters to decompose cover image into 4-Levels (HH, HL, LH and LL) and Discrete Cosine Transforms to convert a signal of the selected coefficients (HH, HL and LH) into elementary frequency components. Simply the proposed hiding method are summarized by dividing the secret data into three sections according to the percentages that have been entered by a user then distribute these sections into the three chosen coefficient sets (HH,HL and LH) of the cover image which is an excellent secure locations for data hiding. The results show the efficiency of the proposed method comparing with other method that used skin tone region of images, DWT method and simple LSB method.